Pengaruh Pemberian Jus Stroberi (Fragaria x ananassa) Terhadap Kerusakan Histologis Sel Hepar Mencit yang Diinduksi Rhodamin B - Pratiwi, Risky; Muthmainah, .; Sari, Yulia (Nexus Biomedika, 2014)
Background: Strawberry contains flavonoid, anthocyanin, ellagic acid and vitamin C that can protect the liver from free radicals. The aims of this research are to know the effect of strawberry juice and the increasing of its dose on the liver histological damage of mice caused by rhodamine B. Methods: This study was laboratory experimental research with the post-test only control group design. The laboratory animal used in this experiment was male Swiss webster mice with 2-3 months old and Â± 20 grams of each weight. Twenty eight samples were divided into 4 groups (KKn, KP, KP1 and KP2), each group consisted of 7 mice. The sampling technique in this research was consecutive sampling. The normal control group (KKn) was given distilled water, while the exposure group (KP), the 1st treatment group (KP1), and 2nd treatment group (KP2) were given rhodamine B. The mice of KP1 and KP2 were given strawberry juice in dose 0.4 ml/20 gWt and 0.8 ml/20 gWt. These treatments were done for 16 days, then on the 17th day mice were killed with neck dislocation and their livers were made for preparation with paraffin block method and stained with HE. Liver cell histological damages were assessed based on quantifying necrotic cells of each 100 cells in the first zone and third zone. The data were analyzed using One-Way ANOVA test and Post Hoc LSD test (Î± = 0.05). Results: The data showed mean of necrotic cells in KKn, KP, KP1 and KP2 were 38.64 Â± 2.56; 157.64 Â± 2.87; 90.07 Â± 2.70; and 68.93 Â± 2.56, repeatedly. The results of One-Way ANOVA test showed p = 0.000. The results of LSD test showed significant difference between KKn-KP, KKn-KP1, KKn-KP2, KP-KP1, KP-KP2, and KP1-KP2 with p = 0.000 for each groups. Conclusion: Strawberry juice reduces miceâs liver cell histological damage caused by rhodamine B and the increasing dose of strawberry juice can reduce liver cell histological damage. Keywords: Strawberry juice, rhodamine B, liver cell histological damageÂ Â